Structural and electrical behavior evaluation of Ho-substituted Co2W hexagonal ferrites. Issue 14 (1st November 2016) - Aen, Faiza; Wasiq, M.F.; Rana, M.U.; Khan, Hasan M.; Khan, Muhammad Azhar
Abstract: Holmium (Ho 3+ ) substituted W-type hexagonal ferrites (BaCo2 Fe16 O27 ) were prepared by sol gel auto-combustion technique. The precursors were prepared by Ba 2+, Fe 3+ nitrates solutions with citric acid as chelating agent. The prepared powder was sintered at 950 °C for 8 h to produce a single phase of W-type hexa ferrite with corresponding crystallite size ranging from 34 nm to 44 nm. The thermal decomposition of nitrate-citrate gel of as-prepared powder was investigated by TGA and DTA. The FTIR spectral study reveals the presence of two absorption bands which are characteristics of hexaferrites. DC electrical resistivity increases from 3.01×10 9 to 5.69×10 10 (ohm-cm). The real and imaginary parts of dielectric constant (ɛʹ, ϵ״) and dielectric loss tangent (tan δ) are determined in the frequency range of 20 Hz–1 MHz. It was observed that both real and imaginary parts of the dielectric constant and tanδ decrease with the increase of frequency on the basis of Wagner and Koop's theory.